The breaststroke start in expert swimmers: A kinematical and coordinative study - Seifert, L.; Payen, V.; Vantorre, J.; Chollet, D. (Biomechanics and Medicine in Swimming X, 2006)
This study used a video camera to compare the kinematics and coordination of the grab Start in one international and eight national breaststroke swimmers at the 100-m pace. The kinematical analysis assessed the durations of leave block, flight, entry and glide, pull-out phases, and the swim up to 15 m. The coordination analysis assessed the time spent with the arm close to the thigh after a complete arm pull-push and the time gap between the end of the arm recovery and the beginning of the leg propulsion. The international swimmer had a shorter 15-m start time than the national swimmers, which was explained by a shorter swim phase, more time in the underwater phase and more time with the arm close to the thigh after the pull-push of the arms. The whole population showed a superposition of two contradictory phases: leg propulsion began whereas the arms were not extended forward because their recovery was not finished